Ethical Research Involving Fetal Human Subjects: American Association of Pro-Life Obstetricians and Gynecologists. (Issues in Law & Medicine)
Fetal tissue research refers to research using several types of tissue, including but not limited to samples obtained from aborted fetuses, cell lines derived from aborted fetuses, and in rarer cases, living previable neonates who have survived an abortion attempt. The ethical questions surrounding each type of tissue procurement are not identical, but do share similarities. This guideline on fetal tissue research discusses the moral status of the human fetus, the state of ethics for medical research on vulnerable subjects, aspects of medical research using human fetal tissue, and the necessity of including fetuses as a protected class under vulnerable populations in research. The debates connected to embryo stem cell research and other research related to embryos are beyond the scope of this document.